Entre a cruz e a crítica: a historiografia e o tempo nas escritas da Academia Brasílica dos Esquecidos (1724- 1725) - Castella, Bruno Vicentini Carneo Ewbank (2025)
This research aims to study how the Academia Brasílica dos Esquecidos, founded in March 1724 in the city of Salvador, begins, based on its writings, a process of “looking at itself” which, in addition to consecrating a new historiographical model, places the brazillian colony as a central part of the Lusitanian Empire, promoting both a unique understanding around the historiographical process and time itself. Despite having had a short period of existence, the Bahian association produced an extensive volume of writings, of which historical dissertations and poems are the focus of this project. Based on some Esquecidos academics, namely Luís Siqueira da Gama, Caetano de Brito e Figueiredo, Gonçalo Soares da Franca and Sebastião da Rocha Pita, this research seeks to analyze their writings as being the result of this nascent Brazilian Enlightenment facet, which had as a fundamental characteristic is the exaltation and consolidation of the Brazilian place. In this way, the construction of this universal history consolidated the imagination of a colony with the qualities of a metropolis, a place whose culture and history would not be subordinate. Therefore, the dissertation intends to be a small contribution with regard not only to eighteenth-century Brazilian academicism, but also to give light to the discussion of a nascent Enlightenment thought in the colony, based on historiography and time